Graphic File Formats: WC130, rev. 4/2021 - Telg, Ricky; McLeod-Morin, Ashley (EDIS, 2021)
This publication on graphic file formats is the fourth of a five-part series on document design. This series also covers the document design process, principles of document design, elements of document design, and brochure and newsletter design. Previous version: Telg, Ricky. 2012. “Graphic File Formats”. EDIS 2012 (7). https://journals.flvc.org/edis/article/view/119921.